Reform des Länderfinanzausgleichs - Thiess Büttner; Johanna Hey; Alfons Weichenrieder; Horst Zimmermann; Stefan Korioth; Martin Junkernheinrich; Wolfgang Renzsch (Wirtschaftsdienst, 2015)
Ende 2019 laufen die bisherigen Regelungen zum Länderfinanzausgleich aus. Zuvor muss eine Reform beschlossen werden. Allerdings sind die Interessen und auch die Belastungssituationen der Geber- und Nehmerländer sehr unterschiedlich. Der Bund kann Mittel bereitstellen, die natürlich begrenzt sind und möglicherweise die Selbstbestimmung der Länder einschränken. Bei den Reformvorschlägen liegt das Schwergewicht entweder auf der Anreizorientierung oder auf der Angleichung der Lebensverhältnisse. Letztlich muss über die Reformmaßnahmen jedoch politisch entschieden werden. Ob dies noch in dieser Legislaturperiode gelingt, ist zweifelhaft. – – At the end of 2019 the regulations of the German fiscal equalisation scheme will expire, i.e. it is absolutely necessary to decide on reforms before this date. But economic interests and the actual burden of donors and recipients differ widely. The federal government can provide financial resources, but they are limited and the provision of resources may restrict the self-determination of the länder. The reform proposals are to some extent based on incentive schemes, e.g. the Scientific Advisory Council at the Federal Ministry of Finance makes the case for a reform that enhances transparency, reduces the disincentives caused by the current distribution formulas and strengthens the capacity to raise own funds, the memebers of the Advisory Council provided simulation results showing that a relatively small amount of block grants would be needed to prevent revenue losses for states with low tax capacity. Others concentrate on the equalization of living conditions. In the end the reforms have to be decided politically. But it is doubtful whether this will happen during the current legislative period.
Keywords: H11; H24; H61; H70; 330; Länderfinanzausgleich; Reform; Deutschland